Remarks on Receiving the 2000 Public Service Award - Judy Sherman (Blackwell Synergy, 2001)
I first received notice that I had been chosen for this award in a letter ... which I opened during a staff meeting. I scanned the letter, reading quickly, and didnÃƒÂ¢Ã¢â€šÂ¬Ã¢â€žÂ¢t take it seriously. I thought it was a message saying something equivalent to ÃƒÂ¢Ã¢â€šÂ¬Ã…â€œI had won some land in Florida.ÃƒÂ¢Ã¢â€šÂ¬Ã‚Â But as the meeting dragged on, I reread the letter and clearly understood what it was saying. To be honored by the people who directly benefit from the lobbying efforts is better than winning land.